Kekuatan Hukum Jual Beli Hak Atas Tanah yang Belum Bersertifikat - Dewa Ayu Mareyta Astri; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2021)
Transfer is a legal act that is intentionally carried out with the aim of transferring land rights from the transferor to receiving the transfer. The formulation of the problem in this study are: 1) What is the mechanism for buying and selling land rights that have not been certified through PPAT? 2) What is the legal force of the deed of sale and purchase of uncertified land rights? Based on the results of the study, it can be concluded that people who sell land that they have sold only have pipil through the PPAT land agency because it is not owned by the state and the mechanism for buying and selling land rights is directed to containing parcels, namely a certificate obtained at PPAT. The legal force of the transfer of land rights by buying and selling on land that has not been legally certified as a sale and purchase of land rights because it has fulfilled the terms of sale and purchase. Generally, what often happens in land transfers that have not been certified by PPAT is passive or in this case only paying attention to written statements from the parties without confirming the truth of the data.